Clinical outcomes in non-surgically managed patients with very severe versus severe aortic stenosis. Issue 24 (27th September 2011) - Kitai, Takeshi; Honda, Satoshi; Okada, Yukikatsu; Tani, Tomoko; Kim, Kitae; Kaji, Shuichiro; Ehara, Natsuhiko; Kinoshita, Makoto; Kobori, Atsushi; Yamamuro, Atsushi; Kita, Toru; Furukawa, Yutaka
Abstract : Objective: The management of asymptomatic severe and very severe aortic stenosis (AS) remains unestablished. This study aimed to investigate the clinical outcomes of severe versus very severe AS patients. Design: A single centre, retrospective cohort study. Patients and Methods: The study retrospectively reviewed 108 conservatively treated patients with severe AS (a maximal jet velocity ≥4.0 m/s, or mean aortic pressure gradient (MPG) ≥40 mm Hg, or an aortic valve area (AVA) <1.0 cm 2 ) and 58 patients with very severe AS (a maximal jet velocity ≥5.0 m/s, or MPG ≥50 mm Hg or an AVA <0.6 cm 2 ). Clinical outcomes were compared between the two groups, considering the existence of symptoms. Main Outcome Measures: All-cause mortality and valve-related event, defined by a composite of cardiac death and hospitalisation because of heart failure. Results: Mean follow-up was 5.5±3.1 years. Fifty-six patients (52%) with severe AS and 20 patients (34%) with very severe AS were asymptomatic. Very severe AS had poorer survival and valve-related event-free survival than severe AS at 3 years (77% vs 88%, p<0.01; 75% vs 88%, p<0.001, respectively). In addition, the 3-year survival and valve-related event-free survival of asymptomatic very severe AS were comparable with symptomatic severe AS, but they were significantly worse than asymptomatic severe AS (p<0.01 and p<0.001, respectively). Conclusions: Surgery should always be considered in very severe AS regardless of symptoms, and particular attention needs to be paid to their extremely poor outcomes.